2023
DOI: 10.5194/wes-8-1-2023
|View full text |Cite
|
Sign up to set email alerts
|

Offshore wind energy forecasting sensitivity to sea surface temperature input in the Mid-Atlantic

Abstract: Abstract. As offshore wind farm development expands, accurate wind resource forecasting over the ocean is needed. One important yet relatively unexplored aspect of offshore wind resource assessment is the role of sea surface temperature (SST). Models are generally forced with reanalysis data sets, which employ daily SST products. Compared with observations, significant variations in SSTs that occur on finer timescales are often not captured. Consequently, shorter-lived events such as sea breezes and low-level … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In terms of evaluating the model's accuracy in forecasting offshore wind, one of the key factors is the SST, as it has a direct impact on atmospheric stability conditions. Though WRF can use the SST input from the relatively coarse initialization data, previous studies like Redfern et al (2023) and Hawbecker et al (2022) [43,44] have performed simulations with external SST inputs, which have a higher resolution compared to the initial and boundary conditions (ICs and BCs). They have observed that the differences in both temporal and spatial resolution between SST products have an impact on wind speed characterization, with higher resolutions tending to enhance model performance.…”
Section: Microphysics Schemementioning
confidence: 99%
“…In terms of evaluating the model's accuracy in forecasting offshore wind, one of the key factors is the SST, as it has a direct impact on atmospheric stability conditions. Though WRF can use the SST input from the relatively coarse initialization data, previous studies like Redfern et al (2023) and Hawbecker et al (2022) [43,44] have performed simulations with external SST inputs, which have a higher resolution compared to the initial and boundary conditions (ICs and BCs). They have observed that the differences in both temporal and spatial resolution between SST products have an impact on wind speed characterization, with higher resolutions tending to enhance model performance.…”
Section: Microphysics Schemementioning
confidence: 99%
“…Constant time steps are set to 18 s and 6 s in the outer and inner domains, respectively. Initial and boundary conditions are also supplied by the hourly 30 km ERA5 dataset (Hersbach et al, 2020) are provided as SST by the UK Met Office Operational Sea Surface Temperature and Sea Ice Analysis dataset (Donlon et al, 2012) and show good agreement during validation against mid-Atlantic bight buoys (Redfern et al, 2023). Physics parameterizations include the MYNN2 planetary boundary layer and surface layer (Nakanishi and Niino, 2006), the Noah Land Surface Model (Niu et al, 2011), the New Thompson microphysics (Thompson et al, 2008), the rapid radiative transfer model for longwave and shortwave radiative transfer (Iacono et al, 2008), and the Kain-Fritsch Cumulus (Kain, 2004) schemes.…”
Section: Now-wakesmentioning
confidence: 99%
“…In terms of evaluating the model's accuracy in forecasting offshore wind, one of the key factors is SST, as it has a direct impact on atmospheric stability conditions. Though WRF can use the SST input from the relatively coarse initialization data, previous studies like Redfern et al (2023) and Hawbecker et al (2022), have performed simulations with external SST inputs which have higher resolution compared to the initial and boundary conditions (ICs and BCs). They have observed that the differences in both temporal and spatial resolution between SST products have an impact on wind speed characterization, with higher resolutions tending to enhance model performance.…”
Section: Offshore Observationsmentioning
confidence: 99%